Mary Wollstonecraft and political economy : the feminist critique of commercial modernity - Packham, Catherine (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2024)
Why was Wollstonecraft's landmark feminist work, the Vindication of the Rights of Woman, categorised as a work of political economy when it was first published? Taking this question as a starting point, Mary Wollstonecraft and Political Economy gives a compelling new account of Wollstonecraft as critic of the material, moral, social, and psychological conditions of commercial modernity. Offering thorough analysis of Wollstonecraft's major writings - including her two Vindications, her novels, her history of the French Revolution, and her travel writing - this is the only book-length study to situate Wollstonecraft in the context of the political economic thought of her time. It shows Wollstonecraft as an economic as much as a political radical, whose critique of the emerging economic orthodoxies of her time anticipates later Romantic thinkers. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.
Introduction: Mary Wollstonecraft and eighteenth-century political economy -- Political economy and commercial society in the 1790s -- The engagement with Burke : contesting the 'natural course of things' -- Property, passions and manners : political economy and the vindications -- Political economy in revolution : France, free commerce and Wollstonecraft's History of the French Revolution -- Property in political economy : modernity, individuation, and literary form -- Credit and credulity : political economy, gender, and the sentiments in The wrongs of woman -- Conclusion: Imagination, futurity, and the value of things.
Title from publisher's bibliographic system (viewed on 15 Feb 2024).
Keywords: Wollstonecraft, Mary, -- 1759-1797 -- Criticism and interpretation; Feminist economics -- Great Britain -- History -- 18th century; Great Britain -- Economic conditions -- 1760-1860.